Implementasi Algoritma Profile Matching Dalam Menentukan Penyakit Menular Pada Hewan Sugar Glider - Pieter Octaviandy; Leony Hoki; Robby Wijaya (Bulletin of Computer Science Research, 2024)
In Indonesia, Sugar Gliders are still not classified as endangered animals, but quotas have been imposed to regulate the capture of Sugar Gliders. The Sugar Glider (Petaurus Breviceps) is a nocturnal marsupial mammal. In addition, Sugar Gliders are often called "pocket pets" because these animals like to live in the pockets of their adopters' clothes. It's called the Sugar Glider because this mammal likes sweet food and can float like a flying squirrel. This ability to levitate is due to a membrane that stretches between its two legs called the Patagium. Even though Sugar Gliders have been kept a lot, most animal lovers do not understand proper care and the types of diseases that can attack Sugar Gliders. In addition, only a small number of veterinarians understand the Sugar Glider thoroughly, and the cost of treatment is quite expensive. The rapid development of computer technology provides convenience in accessing various aspects of life, one of which is the medical field. In this study using the Profile Matching method as a calculation method. This method adheres to multi-variable decision-making with elements of objectives and objectives. The researcher chose this method because Profile Matching considers logical consistency in the assessment used to determine priorities so that there are not many alternatives. Application of Determination of Infectious Diseases in Sugar Glider Animals, which was made using the profile matching method in determining infectious diseases in sugar glider animals. Application for Determination of Infectious Diseases in Sugar Glider Animals which is made with a mobile-accessible system so that use is efficient and fast